Canagliflozin and Cardiovascular and Renal Outcomes in Type 2 Diabetes Mellitus and Chronic Kidney Disease in Primary and Secondary Cardiovascular Prevention Groups: Results From the Randomized CREDENCE Trial. Issue 9 (27th August 2019) - Mahaffey, Kenneth W.; Jardine, Meg J.; Bompoint, Severine; Cannon, Christopher P.; Neal, Bruce; Heerspink, Hiddo J.L.; Charytan, David M.; Edwards, Robert; Agarwal, Rajiv; Bakris, George; Bull, Scott; Capuano, George; et al.
Abstract : Background: Canagliflozin reduces the risk of kidney failure in patients with type 2 diabetes mellitus and chronic kidney disease, but effects on specific cardiovascular outcomes are uncertain, as are effects in people without previous cardiovascular disease (primary prevention). Methods: In CREDENCE (Canagliflozin and Renal Events in Diabetes With Established Nephropathy Clinical Evaluation), 4401 participants with type 2 diabetes mellitus and chronic kidney disease were randomly assigned to canagliflozin or placebo on a background of optimized standard of care. Results: Primary prevention participants (n=2181, 49.6%) were younger (61 versus 65 years), were more often female (37% versus 31%), and had shorter duration of diabetes mellitus (15 years versus 16 years) compared with secondary prevention participants (n=2220, 50.4%). Canagliflozin reduced the risk of major cardiovascular events overall (hazard ratio [HR], 0.80 [95% CI, 0.67–0.95]; P =0.01), with consistent reductions in both the primary (HR, 0.68 [95% CI, 0.49–0.94]) and secondary (HR, 0.85 [95% CI, 0.69–1.06]) prevention groups ( P for interaction=0.25). Effects were also similar for the components of the composite including cardiovascular death (HR, 0.78 [95% CI, 0.61–1.00]), nonfatal myocardial infarction (HR, 0.81 [95% CI, 0.59–1.10]), and nonfatal stroke (HR, 0.80 [95% CI, 0.56–1.15]). The risk of the primary composite renal outcome and the composite of cardiovascular death or hospitalization for heart failure were also consistently reduced in both the primary and secondary prevention groups ( P for interaction >0.5 for each outcome). Conclusions: Canagliflozin significantly reduced major cardiovascular events and kidney failure in patients with type 2 diabetes mellitus and chronic kidney disease, including in participants who did not have previous cardiovascular disease. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02065791. Abstract : Supplemental Digital Content is available in the text.